New family medicine residency training programme: Residents' perspectives from the University of Botswana - Deogratias O. Mbuka; Stephane Tshitenge; Vincent Setlhare; Billy Tsima; Ganiyu Adewale; Luise Parsons (AOSIS, 2016)
Background: Family Medicine (FM) training is new in Botswana. No previous evaluation of the experiences and opinions of residents of the University of Botswana (UB) Family Medicine training programme has been reported.Aims: This study explored and assessed residents' experiences and satisfaction with the FM training programme at the UB and solicited potential strategies for improvement from the residents. Methods: A descriptive survey using a self-administered questionnaire based on a Likert-type scale and open-ended questions was used to collect data from FM residents at the UB. Results: Eight out the 14 eligible residents participated to this study. Generally, residents were not satisfied with the FM training programme. Staff shortage, inadequate supervision and poor programme organisation by the faculty were the main reasons for this. However, the residents were satisfied with weekly training schedules and the diversity of patients in the current training sites. Residents' potential solutions included an increase in staff, the acquisition of equipment at teaching sites and emphasis on FM core topics teachings. They had different views regarding how certain future career paths will be. Conclusions: Despite the general dissatisfaction among residents because of challenges faced by the training programme, we have learnt that residents are capable of valuable inputs for improvement of their programme when engaged. There is need for the Department of Family Medicine to work with the Ministry of Health to set a clear career pathway for future graduates and to reflect on residents' input for possible implementation.